Comparison of Histopathological Analysis of Autologous Fat Tissue, Cerebrospinal Fluid and Sodium Hyaluronate for Preventing Epidural Fibrosis - Balci, Burak Bilal; Taşkapılıoğlu, Mevlüt Özgür; Özmen, Özlem; Salci, Hakan (Acta Scientiae Veterinariae, 2025)
Background: Decompressive surgery is an operative procedure performed to prevent the compression to the spinal cord or the other neural tissues. Laminectomy as a decompressive technique is applied to widening the spinal canal resulted from secondary to fractures, tumors, abscesses and deformities. Epidural fibrosis (EF) is a progressive formation. While the epidural hematoma in the spinal region is absorbed, it gradually occurs the granulation tissue and then this turns into the fibrous tissue. This fibrous tissue replaces the bone excised in laminectomy and attaches to the muscles overlying the dura mater. EF compress to the surrounding neural tissues and nerve roots, and cause to neuronal atrophy and axonal degeneration. This study aims to compare histopathological results of autologous fat tissue, cerebrospinal fluid (CSF) and sodium hyaluronate for preventing epidural fibrosis (EF). Materials, Methods & Results: Totally, 20 (n=20) Wistar Albino rats were randomly selected and the study was carried out in 4 groups with equal numbers of rats (5) in each group. Under general anesthesia, laminectomy was performed on L3 vertebral lamina in all groups. Biomaterials applicated to the laminectomy area were saline in GRI, autologous fat tissue in GRII, 0.1 mL CSF in GRIII and 0.1 mL sodium hyaluronate in GRIV. Lateral and ventrodorsal lumbar radiographs were taken from all rats before and after surgery. Tarlov’s motor function tests were scored in groups pre- and postoperatively. At postoperative 45 day, the L2-4 spine segments of the rats were en-bloc removed and the prepared slides were stained with hematoxylin and eosin. Microscopically, fibroblastic density, EF, arachnoid fibrosis and inflammatory cell infiltration were evaluated. The obtained data were evaluated statistically. On control days, all rats gait was normal in GRI, GRIII and GRIV; however, In GRII, Tarlov’s score was 2 in a rat. There was no significant difference in terms of measurement times of Tarlov’s motor function scoring within and between groups (P > 0.05). Fibroblastic density, EF, arachnoid fibrosis and inflammatory cell scores were the most severe and dense in GRI. These were less in GRII and GRIV, and fibroblastic and inflammatory cell findings were the least in GRIII. Statistically significant differences were found between GRI and GRIII in terms of fibroblast density (P = 0.002), epidural fibrosis (P = 0.002), arachnoid fibrosis (P = 0.001) and inflammatory cell infiltration (P = 0.003). There was no statistically significant difference between the other study groups (P > 0.05). Discussion: Clinically, the presence of pain in patients who have undergone laminectomy is scored and neurological findings are evaluated with functional tests. Macroscopic examination of the dura mater and surrounding tissues is not sufficient to determine the degree of epidural adhesions and therefore experimental histopathological studies are required. Although easily obtained, the positive effect of autologous fat grafts in preventing EF is still controversial. Compared to plasma, the low potassium concentration of CSF appears to play a role in preventing fibrosis by suppressing the ability of fibroblasts to attach and spread. Exogenously applied hyaluronic acid inhibits fibroblast proliferation and reduces fibrosis and scar formation in the early stages of tissue healing. However, considering the data of this study, CSF was the most effective biomaterial in reducing fibroblastic density and preventing EF in the laminectomy area. Keywords: EF, CSF, laminectomy, biomaterial, epidural fibrosis, motor function test, histopathology, Wistar Albino rats.